2022
DOI: 10.1136/bjophthalmol-2021-320046
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of ocular biometric parameters with onset and progression of diabetic retinopathy in Chinese adults with type 2 diabetes mellitus

Abstract: AimsTo investigate the associations of ocular biometric parameters with incident diabetic retinopathy (DR), incident vision-threatening DR (VTDR) and DR progression.MethodsThis community-based prospective cohort study recruited participants with type 2 diabetes aged 35–80 years from 2017 to 2019 in Guangzhou, China. Refractive error and ocular biometric parameters were measured at baseline, including axial length (AL), axial length-to-corneal radius (AL/CR) ratio, corneal curvature (CC), lens thickness (LT), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This may partly explain why patients with DM with high myopia have a lower risk of developing DR, as the choroidal blood flow of highly myopic eyes is much lower than that of emmetropic eyes. 17,29 Our results highlight the potential value of longitudinal changes in OCT ocular parameters on monitoring and early prediction of DR onset. Currently, the monitoring and evaluation of DR onset are based on ocular and systemic risk factors that were identified through crosssectional studies and fluctuate with various confounding factors.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This may partly explain why patients with DM with high myopia have a lower risk of developing DR, as the choroidal blood flow of highly myopic eyes is much lower than that of emmetropic eyes. 17,29 Our results highlight the potential value of longitudinal changes in OCT ocular parameters on monitoring and early prediction of DR onset. Currently, the monitoring and evaluation of DR onset are based on ocular and systemic risk factors that were identified through crosssectional studies and fluctuate with various confounding factors.…”
Section: Discussionmentioning
confidence: 61%
“…This may partly explain why patients with DM with high myopia have a lower risk of developing DR, as the choroidal blood flow of highly myopic eyes is much lower than that of emmetropic eyes. 17,29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the occurrence and progression of DR are correlated with a longer period of diabetes, higher blood glucose, blood pressure, and serum glycosylated hemoglobin levels ( 6 ). In addition to these systemic risk factors, some studies ( 7 , 8 ) have found that ocular biological parameters can also influence the occurrence and progression of DR, although this assertion is controversial. Lim et al ( 7 ) discovered that diabetic patients with myopic refractive errors and long eye axes had a decreased risk of developing DR, particularly proliferative diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found no difference in keratometric readings between diabetic and non-diabetic groups [ 8 , 9 ]. A small number of studies reported that the corneal curvature radius changes in diabetic people [ 10 ]. According to other studies, diabetic patients have higher keratometry values while corneal topography indices do not differ between diabetics and non-diabetics [ 11 – 13 ].…”
Section: Introductionmentioning
confidence: 99%